Ammianus Marcellinus : an annotated bibliography, 1474 to the present - Jenkins, Fred W. (Philological and Historical Commentary on Ammianus Marcellinus., 2017)
In Ammianus Marcellinus: An Annotated Bibliography, 1474 to the Present , Fred W. Jenkins surveys scholarship on Ammianus from the editio princeps to the present. Included are bibliographies, editions, translations, commentaries, concordances and indexes, Web sites, and secondary scholarship in many languages.